Hubungan Personal Hygiene dan Masa Kerja Dengan Kejadian Dermatitis Akibat Limbah B3 Pada Mekanik Bengkel Di Kecamatan Way Serdang - Vikto Agus Wibowo; Aulia Ulmillah; Nurhaida Widiani (UIN Sunan Gunung Djati Bandung, 2021)
Personal hygiene aims to maintain the cleanliness and health of workshop mechanics who are at risk of being exposed to B3 waste in their daily work. Long exposure and working priod can cause dermatitis in workers. Therefore, this study aims to determine the relationship between personal hygiene and tenure with the incidence of dermatitis. This qualitative research was conducted in 4 villages in Way Serdang sub-district. Sampling was done by purposive sampling through a cross sectional approach and data collection was done by structured interview. The results showed that the incidence of dermatitis was only related to Personal Hygiene.